Forests: Beyond Timber - Arce, Arce (2022)
The purpose of this article is to reflect on the implications of recognizing the intrinsic value of life in forests and, to this end, it proposes a forestry vision beyond timber; it takes as a reference the contributions of the Colombian philosopher Carlos Maldonado and complements them with the contributions of the process "Towards a new Forestry Policy for Peru" in which the author acted as a systematiser. It is found that the denomination of forest resources obeys an economicist conception sustained by a disjunctive form of human relationship with forests. The currents of nature conservation indicate that there is a biocentric turn that overcomes the anthropocentric ethic that has prevailed to date. Hence the need to broaden the forest concept reduced to timber. From the reflection it is concluded that the incorporation of an expanded vision of forest sciences includes the recognition of the value of non-human life in forests, a novel and transforming process in accordance with the evolution of the understanding of the relationships between nature (forests) and human beings. The maintenance, on the one hand, of a strongly reductionist, disjunctive, mechanistic, deterministic forestry science, and on the other hand the timber bias, has deprived further development in other important fields of human welfare and human security, in tune with the advancement of the recognition of the rights of nature, animal rights and the recognition of sensitivity and intelligence in plants.